Antimicrobial and Cytotoxic Properties of the Ascidians Lissoclinum patella, Oxycoryna fascicularis, Didemnum molle and Botryllus schlosseri - Karim, Firmansyah; Putra, Masteria Yunovilsa; Hadi, Tri Aryono; Abrar, Muhammad (UI Scholars Hub, 2018)
The aim of this research is to investigate antimicrobial and cytotoxic activity from Indonesian ascidians. Extracts prepared from the Indonesian ascidians Lissoclinum patella, Oxycoryna fascicularis, Didemnum molle and Botryllus schlosseri were assessed for anti-microbial and cytotoxic properties. Antibacterial activity of the extracts was tested against two Gram-positive bacteria, viz. Bacillus subtilis ATCC 6633 and Staphylococcus aureus ATCC 25923, and three Gram-negative bacteria, viz. Escherichia coli ATCC 25922, Vibrio cholerae ATCC 14035 and Pseudomonas aeruginosa ATCC 101454 using the disk diffusion test. Antifungal activity was also tested against Candida albicans ATCC 10231 and Aspergillus niger ATCC 16404. The minimum inhibitory concentrations (MICs) of potential ascidian extracts were determined by the microdilution technique. Cytotoxicity of the extracts was assessed using the brine shrimp lethality bioassay. By comparing the inhibition zones in the disk diffusion test, the most active anti-bacterial activity against Gram-positive bacteria (S. aureus and B. subtilis) was found in the crude extracts of Oxycoryna fascicularis and Didemnum molle. Lissoclinum patella extract showed the highest activity against the Gram-negative bacteria E. coli and V. cholerae. The LC50 values of the crude extracts of Lissoclinum patella, Didemnum molle, Botryllus schlosseri, and Oxycoryna fascicularis were 74.3, 97.2, 114.7 and 132.9 μg/ml, respectively. In our study, the most promising species for anti-microbial and cytotoxic properties are Lissoclinum patella and Didemnum molle.